KERJASAMA UNODC – INDONESIA DALAM MEMERANGI PERDAGANGAN MANUSIA PERIODE 2007-2013 - Rahardianto, Tahta Dika; Utomo, Tri Cahyo; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
The impact of technological advancement does not always has apositive effect. For example, one of the negative impact is the growingforms of transnational crime such as human trafficking. As onecontinent from five continents in the world, Asia is the region with thenumber of victims of human trafficking at most. Indonesia is one ofAsian countries which has become a source, destination, and transit ofhuman trafficking. Surely the Government of Indonesia continues tostrive to combat human trafficking in various ways, one of them ispartnership with UNODC. This thesis aims to determine the form ofthe partnership between the Government of Indonesia with theUNODC in combating human trafficking with period 2007-2013. Inthis thesis, author use the theory of Liberalism Institutionalism,because it is considered the most appropriate theory to explain thecooperation between the Government of Indonesia and UNODC. Inthis thesis, author use descriptive-explanative research type to explainand to describe the phenomenon of human trafficking in Indonesia.The results from this research is that the cooperation between theGovernment of Indonesia and UNODC are effective and inaccordance with the needs of the Government of Indonesia especiallyon the aspect of capacity building of Indonesian law enforcementofficial. However, the result from this cooperation does not give apositive implication for the reduction of the number of victims ofhuman trafficking in Indonesia.